2017
DOI: 10.1016/j.bmc.2017.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Indole-TEMPO conjugates alleviate ischemia-reperfusion injury via attenuation of oxidative stress and preservation of mitochondrial function

Abstract: Mitochondrial oxidative damage contributes to a wide range of pathologies including ischemia/reperfusion injury. Accordingly, protecting mitochondria from oxidative damage should possess therapeutic relevance. In the present study, we have designed and synthesized a series of novel indole-TEMPO conjugates that manifested good anti-inflammatory properties in a murine model of xylene-induced ear edema. We have demonstrated that these compounds can protect cells from simulated ischemia/reperfusion (s-I/R)-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Initially, we evaluated the antioxidant effects of IADB , alone or in combination with 5-FU, in the control H9C2 rat cardiomyoblasts and the colon cancer cell line HT-29. We employed MitoProbe, a sensitive fluorogenic reporter, for real-time monitoring of mitochondrial ROS (mtROS) generation. The MFI of MitoProbe was quantified as a gauge of mtROS production.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we evaluated the antioxidant effects of IADB , alone or in combination with 5-FU, in the control H9C2 rat cardiomyoblasts and the colon cancer cell line HT-29. We employed MitoProbe, a sensitive fluorogenic reporter, for real-time monitoring of mitochondrial ROS (mtROS) generation. The MFI of MitoProbe was quantified as a gauge of mtROS production.…”
Section: Resultsmentioning
confidence: 99%
“…b-carbolines are biologically active alkaloids, and these compounds have been reported to possess a wide range of biological effects, such as anti-inflammatory, antithrombotic activities, antivirus, anticancer and free radical scavenging activities [46]. Previous studies demonstrated the potential application of b-carboline derivatives in the treatment of cardiovascular diseases like hypertension [47], myocardial infarction [25], [48], cancer [49][50][51][52], and ischemia/reperfusion injury [53][54][55][56][57][58][59]. In addition, 4-hydroxy-2,2,6,6-tetramethyl-piperidine-N-oxyl (Tempol) has gained attention.…”
Section: Discussionmentioning
confidence: 99%
“…To monitor mitochondrial ROS production during H/R, H9C2 cells were labeled with MitoProbe (a fluorogenic dye that is highly sensitive for monitoring mtROS [33][34][35][36][37][38][39]). Through measurement of the MFI of MitoProbe at different time points of H/R, the total amount of mtROS could be estimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The indole derivatives have been reported to possess anti-inflammatory, free radical scavenging activity, mitochondrial protection, and autophagy-modulating activity. [50][51][52][53][54][55] For example, IADB, a novel indole alkaloid-nitroxide conjugate, has been reported to exert mitochondrial protection and cardio-protection through its autophagy-modulating potential. 52 In our present study, we attempted to further examine the role of IADB in the SOD1 G93A -associated experimental models of ALS.…”
Section: Introductionmentioning
confidence: 99%